Ab-initio calculation of charged defects in ZnO using the program CRYSTAL - Ыбыраев, Н.С.; Усеинов, А.Б.; Акылбеков, А.Т.; Здоровец, М.В.; Оралбеков, Н.Б.; Дукенов, А.Б. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
in the paper, ab-initio calculations were performed in the LCAO approximation using the CRYSTAL14 program for charged defects in zinc oxide. It is shown that at a high concentration of defects (close to the location of defects), an underestimation of the energy of formation is observed in connection with a significant delocalization of the charge in the crystal cell. The inclusion of bias correction and defect-defective interaction improves the readings in comparison with the formation energy in a large supercell. However, as studies have shown, it is also necessary to take into account the covalent dimensions of impurity atoms in the defect-defect interaction. The obtained results are in good agreement with the previous theoretical works, in which other calculation methods were used and are capable of qualitatively describing the energy characteristics of the defects.